ХАРАКТЕРИСТИКА ОСІБ, ЯКІ ЗАЙМАЮТЬСЯ СЕКСУАЛЬНОЮ ЕКСПЛУАТАЦІЄЮ - Нєбитов, Андрій Анатолійович (SUPREMANCE OF LAW, 2016)
The paper studied the concept of offender, offender characteristics and personality characterized perpetrators of sexual exploitation. It is proved that the qualitative criminological harakteristika offender allows you to develop and effectively realizovat measures to prevent this type of crime.